Reply to Comment on 'Imaging of prompt gamma rays emitted during delivery of clinical proton beams with a Compton camera: feasibility studies for range verification'. (2nd December 2016) - Polf, Jerimy C; Avery, Stephen; Mackin, Dennis S; Beddar, Sam
Abstract: A reply is provided to the points raised in the comment by Dr Sitek (2016 Phys. Med. Biol . 61 8941 ) on Polf et al (2015 Phys. Med. Biol . 60 7085 ).